UPAYA PENANGGULANGAN BENCANA ALAM GEMPA BUMI DI LEMBAGA PEMASYARAKATAN DI TINJAU DARI KEPDIRJENPAS NO. 57 TAHUN 2019 - AZKA, AQORI SATRIA (Journal of Correctional Studies, 2024)
The article entitled "Earthquake Natural Disaster Management Efforts in Correctional Institutions Reviewed by Kepdirjenpas No. 57 of 2019" has significant implications in the context of natural disaster risk management and mitigation in correctional institutions. Kepdirjenpas No. 57 of 2019 is a regulation that regulates the guidelines for the implementation of disaster management in correctional institutions in Indonesia. The implications of this title cover various aspects relating to post-earthquake preparation, response and recovery. In this article, the review will discuss these implications in full and detail. This article uses a qualitative research method using literature review in providing the results of the study. Overall, the title of this article has broad implications for improving safety and natural disaster risk mitigation in correctional institutions. The implementation of Kepdirjenpas No. 57/2019 is an important step in meeting these challenges and maintaining the safety of detainees, staff and the integrity of facilities in risky environments such as correctional institutions